2019
DOI: 10.1371/journal.pone.0220723
|View full text |Cite
|
Sign up to set email alerts
|

Does economic inequality moderate the effect of class on prosocial behavior? A large-scale test of a recent hypothesis by Côté et al

Abstract: Empirical research has provided mixed evidence regarding the question of whether higher social class promotes prosocial behavior. Recently, Côté et al. [ 1 ] hypothesized that these conflicting evidences might result from a hitherto neglected interaction between the individual’s level of income and the degree of inequality in one’s society. They argue that societies with a higher level of inequality foster a sense of entitlement in high-income individuals, which in turn leads them to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
(29 reference statements)
2
26
0
2
Order By: Relevance
“…These data from a battery of real-world experiments lend more weight to the hypothesis that relative deprivation is negatively associated with generalized trust and prosociality. Several other studies have reported a similar pattern [34,[52][53][54][55][56][57][58][59][60][61]. In experimental settings, exposure to harsh environments has been associated with an increased willingness to defect in a Prisoner's Dilemma game, and a reduced tendency to send money to a partner in a Dictator Game [36,62,63], and experimentally induced financial deprivation can increase the willingness to cheat for financial rewards [64].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These data from a battery of real-world experiments lend more weight to the hypothesis that relative deprivation is negatively associated with generalized trust and prosociality. Several other studies have reported a similar pattern [34,[52][53][54][55][56][57][58][59][60][61]. In experimental settings, exposure to harsh environments has been associated with an increased willingness to defect in a Prisoner's Dilemma game, and a reduced tendency to send money to a partner in a Dictator Game [36,62,63], and experimentally induced financial deprivation can increase the willingness to cheat for financial rewards [64].…”
Section: Discussionmentioning
confidence: 63%
“…Large-scale, survey-based studies report similar findings. One recent study using more than 30 000 observations based on nationally representative samples concluded that high socio-economic status was associated with increased willingness to donate to charity, to volunteer to help, to contribute a higher proportion of income to charity, and to choose the prosocial option in an economic game [59] (see also [58]), while another large study (a total sample of greater than 60 000 and with participants from more than 30 countries) reported positive effects of household income on tendency to volunteer or to donate to charity ( [60], but see [65], who performed a similar study, obtaining a null result). Finally, a study using data from more than 40 000 responses to the World Values Survey and the European Values Study, respectively, also suggests a negative link between exposure to environmental harshness and the tendency to invest in cooperative behaviour [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous research offers convincing evidence for the negative relationship between relative financial standing and prosocial behavior, some studies have demonstrated a reverse pattern. Two large-scale studies reported a positive relationship between objective and subjective social class and self-reported charitable donations (Korndörfer, Egloff, & Schmukle, 2015;von Hermanni & Tuti c, 2019) and volunteering (von Hermanni & Tuti c, 2019). Another study examined the effect of the interaction between income and inequality on generosity in three large representative datasets.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent large-scale studies have found no such moderating effect in other populations (von Hermanni & Tutić, 2019;Schmukle et al, 2019). In our studies, we collected measures of objective and subjective socioeconomic status, as well geographical data, allowing us to examine the overall relationship between social rank and prosociality and whether this is moderated by the inequality in the participant's home state.…”
mentioning
confidence: 99%